The Effect of Pre-Sowing Treatments on Seed Germination of Erythrina humeana Spreng (Libyan Journal of Ecological & Environmental Sciences and Technology, 2019)
This study was carried out to investigate the effect of pre-sowing treatments on seed germination of Erythrina humeana Spreng. The Cold water-treated seeds were soaked in distilled water for 24 hours, hot water-treated seeds were soaked in boiled water (away from heat source) for 24 hours, seeds were immersed in 98% sulphuric acid for 5 minutes (SA 98%-5M), and sulphuric acid 98% treatment seeds were immersed for 15 minutes (SA 98%-15M). Erythrina humeana Spreng grown in the campus of Omar Al-Mukhtar university Albyda, Libya. The following germination parameters were determined: Germination Percentage (GP), Mean Germination Time (MGT), Germination Index (GI), and root length.  One-way analysis of variance (ANOVA) was conducted to confirm the variability and validity of the data. The result showed the highest germination was recorded when seeds were treated with hot water and SA 98%-15M. MGT showed no statistical differences observed among the pre-sowing treatments. However, the cold water and SA 98%-5M treatments significantly decreased the GI in Erythrina humeana Spreng. Result found that root length of the seedlings developed under treatments was highest (1.765 cm) in hot water treatment followed by SA 98%-15M treatment (1.35 cm). In the conclusion of the study it was indicated that the hot water and SA 98%-15M treatments break dormancy and promote germination of Erythrina humeana Spreng. The present study will be useful to screen other pre-sowing treatments such as immersing seeds of Erythrina humeana Spreng in absolute sulphuric acid for 20, 25 ,30 and 60 minutes. Further work is required to develop the pre-sowing treatments to ensure high germination ratio in the field.
Keywords: coral tree; Germination Percentage; Pre-sowing treatments